Engineering of TMDC–OSC hybrid interfaces: the thermodynamics of unitary and mixed acene monolayers on MoS2 - Kachel, Stefan R; Pierre-Martin Dombrowski; Breuer, Tobias; Gottfried, J Michael; Witte, Gregor (Chemical science (Cambridge), 2021)
Hybrid systems of two-dimensional (2D) materials such as transition metal dichalcogenides (TMDCs) and organic semiconductors (OSCs) have become subject of great interest for future device architectures. Although OSC–TMDC hybrid systems have been used in first device demonstrations, the precise preparation of ultra-thin OSC films on TMDCs has not been addressed. Due to the weak van der Waals interaction between TMDCs and OSCs, this requires precise knowledge of the thermodynamics at hand. Here, we use temperature-programmed desorption (TPD) and Monte Carlo (MC) simulations of TPD traces to characterize the desorption kinetics of pentacene (PEN) and perfluoropentacene (PFP) on MoS2 as a model system for OSCs on TMDCs. We show that the monolayers of PEN and PFP are thermally stabilized compared to their multilayers, which allows preparation of nominal monolayers by selective desorption of multilayers. This stabilization is, however, caused by entropy due to a high molecular mobility rather than an enhanced molecule–substrate bond. Consequently, the nominal monolayers are not densely packed films. Molecular mobility can be suppressed in mixed monolayers of PEN and PFP that, due to intermolecular attraction, form highly ordered films as shown by scanning tunneling microscopy. Although this reduces the entropic stabilization, the intermolecular attraction further stabilizes mixed films.